Use of gis for small-scale hydropower development in Tajikistan (Journal of Geography and Environmental Management, 2016)
A reliable year-round energy supply is a precondition for economic development. Without such provision, Tajikistan will remain unattractive to investors operating in sectors such as manufacturing, technology, and value-added processing. Considering Tajikistan’s ample waterresources, the development of small-scale hydropower plants (SSHP) (500 kW – 10 MW) is considered essential for establishing a sustainable local economy in the country. In order for investors to engage in Tajikistan’s small-scale hydropower sector, however, several steps have to be undertaken, which include: 1) the creation of an attractive and stable market environment; 2) the establishment of a transparent regulatory and commercial framework; and 3) the development of a readily accessibleknowledge-base facilitating planning and construction of small scale hydropower plants (SSHP). Within this project, a Geographical Information Systems (GIS) was applied for several different purposes. The most basic task was to put the existing and potential hydropower schemes into a geographical context i.e. georeferencing the basic scheme components such as intake, headrace channel, powerhouse etc. For each site, based on a digital ASTER terrain model, the catchment and its characteristic parameters including size, glacier coverage, exposition and altitude distribution was derived. The same geo-analysis was conducted forselected hydrological observation stations for which aggregated historic mean monthly discharge data were available. Comparative catchment analysis allowed indicative run-off estimates at the ungauged potentialhydropower sites. GIS was furthermore used to assess the feasibility and resulting construction cost of the potential sites. Relevant factors include potential gradient, distance to access roads and to the closest electrical grid uplink. The visualization of the schemes in GoogleEarth allowed remote initial assessments of the sites regarding natural hazards (landslides, avalanches etc.) and potential water user conflicts.
Keywords: GIS; hydropower; geoprocessing; geodata